Application of the Principles of Coordination between Polri Investigators and Prosecutors in Processing Criminal Cases in the Legal Territory of the Pontianak Police, West Kalimantan City - Fery Suryono; Kawakib Kawakib (JED (Jurnal Etika Demokrasi), 2022)
The purpose of this article is to find out the actual duties and authorities of the implementation of the principle of coordination between the police investigators and prosecutors in the process of handling criminal cases in law enforcement agencies as regulated in the Criminal Procedure Code because in practice in the field it is often found that in handling crime problems there are no following reality and in the end investigators and public prosecutors gave rise to a negative stigma in the judge's decision. The type of research methodology in this article is normative juridical. Normative legal research focuses on doctrine by analyzing legal rules found in statutory regulations or various judges' decisions. The data presented are descriptive and analytical symptoms that occur in the field, namely between investigators, public prosecutors, and judges with the rule of law or actions with norms according to legal principles. Therefore, the obstacles that limit the implementation of the principle of coordination between Polri investigators and the public prosecutor include The lack of communication and coordination between the Polri and the public prosecutor because those who prioritize the interests of their institutions without paying attention to the interests of other parties, and lack of trust in Polri and other law enforcers, as is the stigma that grows in the community today, makes it difficult for the Police to carry out their duties in the field; neglect of resource aspects in law enforcement; not yet the same vision and opinion of law enforcers; and have not understood the doctrine, professional ethics of the Police by investigators causing the morale of the investigators to below, in addition to problems with welfare, equipment, and limited investigative funds.Tujuan artikel ini penulis ingin mengetahui tugas dan wewenang yang sebenarnya terhadap penerapan asas koordinasi penyidik polri dengan jaksa dalam proses menangani kriminalisasi perkara pidana diwilah penegak hukum sebagaimana yang telah diatur dalam Undang-Undang KUHAP, karena prakteknya dilapangan seringkali ditemukan bahwa dalam penanganan permasalahan tindak pidana tidak sesuai dengan kenyataan dan pada akhirnya penyidik dan jaksa penuntut umum memunculkan stigma negatif dalam putusan hakim. Jenis metodologi penelitian artikel ini bersifat yuridis normatif  yaitu; penelitian hukum normatif berfokus pada doktrin melalui analisis kaidah hukum yang ditemukan dalam peraturan perundang-undangan atau dalam berbagai putusan hakim. Data yang disajikan bersifat deskriptif dan analitis yaitu gejala yang terjadi di langan yaitu anatara penyidik, jaksa penuntut umum dan hakim dengan aturan hukum atau tindakan dengan norma-norma sesuai prinsip hukum. Oleh karena itu, kendala-kendala yang membatasi pelaksanaan asas koordinasi antara penyidik Polri dengan Jaksa Penuntut umum antara lain: Minimnya komunikasi dan koordinasi antara Polri serta jaksa penutut umum, karena yang lebih mengedepankan kepentingan lembagnya sendiri tanpa mencermati kepentingan pihak lain, serta kekurang percayaan kepada Polri serta penegak hukum yang lain, sebagaimana stigma yang tumbuh di warga dikala ini menyebabkan Polri kesuitan dalam melaksanakan tugas di lapangan; pengabaian aspek sumberdaya dalam penegakan hukum; belum samanya visi serta anggapan para penegak hukum; serta belum difakami doktrin, etika profesi Kepolisian oleh penyidik menyebabkan moral aparat penyidik rendah, disamping itu permasalahan kesejahteraan, perlengkapan, dana penyidikan yang terbatas